2017
DOI: 10.1002/1873-3468.12694
|View full text |Cite
|
Sign up to set email alerts
|

Quorum sensing in Candida albicans: farnesol versus farnesoic acid

Abstract: Read the Original article at doi: 10.1002/1873-3468.12636.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
(38 reference statements)
0
13
0
Order By: Relevance
“…Further studies should clarify and differentiate the metabolic pathways and cellular mechanisms involved in QS from those involved in biofilm toxicity. In this context, it would be appropriate to investigate the consequences of farnesol conversion to farnesoic acid with respect to biofilm formation, as previously described in C. albicans ATCC 10231 (29).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies should clarify and differentiate the metabolic pathways and cellular mechanisms involved in QS from those involved in biofilm toxicity. In this context, it would be appropriate to investigate the consequences of farnesol conversion to farnesoic acid with respect to biofilm formation, as previously described in C. albicans ATCC 10231 (29).…”
Section: Discussionmentioning
confidence: 99%
“…Farnesol is also a quorum-sensing molecule but produced as a secondary product of sterol biosynthesis and secreted by C. albicans ( 118 ). When accumulated, it prevents the formation of filamentous growth and biofilm ( 119 122 ). Generally, farnesol is mostly secreted in the later stages of biofilm formation by C. albicans ( 122 ).…”
Section: The Challengesmentioning
confidence: 99%
“…Along with farnesol, a few other molecules produced by C. albicans have been proposed to work as quorum-sensing molecules, including morphogenic autoregulatory substance, phenylethyl alcohol and tryptophol ( 127 ), tyrosol, and farnesoic acid. Although through different pathways, farnesoic acid, just like farnesol, is involved in regulating the yeast-to-hyphae transition ( 119 , 127 ). Depending on the strain, C. albicans might produce farnesol or farnesoic acid, both having an inhibitory effect of filamentous growth ( 127 ).…”
Section: The Challengesmentioning
confidence: 99%
“…According to Riekhof and Nickerson (2017), it has been demonstrated that C. albicans is a dimorphic fungus in the presence of farnesoic acid (FA) and farnesol (F), the two sensor molecules of related sesquiterpene quorums, and when accumulated, they do not allow the change from yeast to mycelium. Studies were conducted with three different ATCC strains of C. albicans, 10231, A72, and SC5314.…”
Section: Quorum Sensing (Qs)mentioning
confidence: 99%